The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/jp301908c
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Acid/Base and Structural Properties of Titanate-Loaded Mesoporous Silica by Grafting of Zinc Oxide

Abstract: Mesoporous silica (SBA-15) loaded with TiO x species was synthesized by anhydrous grafting of titanium isopropoxide, and a novel procedure for the preparation of ZnO x /SBA-15 materials by grafting of Zn(acac) 2 was explored.The TiO x /SBA-15 and ZnO x /SBA-15 materials as well as subsequently prepared bifunctional ZnO x -and TiO x -containing SBA-15 materials were characterized in depth by combining N 2 physisorption measurements, UV−vis, X-ray photoelectron and Xray absorption spectroscopy, and CO 2 and NH 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 53 publications
2
39
1
Order By: Relevance
“…The latter (1024.7 eV) showed a positive shift (3.6 eV) in comparison with the former (1021.1 eV), indicating a decrease in the outer electron cloud density of Zn 2+ . Such behavior was observed by Tkachenko et al and Mei et al, and they ascribed the peak with the higher binding energy to ZnO x . , However, no further evidence in this study confirmed the formation of a ZnO x species. According to the FT-IR results showed in Figure a, this peak was confirmed to be related to the monodentate ZnCO 3 species.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The latter (1024.7 eV) showed a positive shift (3.6 eV) in comparison with the former (1021.1 eV), indicating a decrease in the outer electron cloud density of Zn 2+ . Such behavior was observed by Tkachenko et al and Mei et al, and they ascribed the peak with the higher binding energy to ZnO x . , However, no further evidence in this study confirmed the formation of a ZnO x species. According to the FT-IR results showed in Figure a, this peak was confirmed to be related to the monodentate ZnCO 3 species.…”
Section: Resultssupporting
confidence: 66%
“…Such behavior was observed by Tkachenko et al and Mei et al, and they ascribed the peak with the higher binding energy to ZnO x . 39,40 However, no further evidence in this study confirmed the formation of a ZnO x species. According to the FT-IR results showed in Figure 4a, this peak was confirmed to be related to the monodentate ZnCO 3 species.…”
Section: ■ Experimental Sectioncontrasting
confidence: 70%
“…Figure4B shows that on increasing the zinc content in the Pt-Zn/SBA-15 series, the white line intensity decreases and the peak splits into a strong doublet which agrees with the results which have been previously reported by Mei et al who attributed the formation of [ZnO4] 6on silica surfaces. 37 The similarity in lattice and coordination number matching with internal silica surface appears to offer a strong directing role to bind Zn ions preferentially from the mixture of Pt and Zn precursors. Analysis of the Zn K edge EXAFS demonstrates there is no long range ordered structure present in the local coordination environment of the Zn atoms.…”
Section: Resultsmentioning
confidence: 99%
“…For low vanadium oxide (VO x ) loadings (up to about 1 V nm –2 ), the specific surface area (SSA) of the catalysts is hardly affected by the VO x layer, whereas higher loadings lead to a decrease of the SSA. This decrease in SSA might be attributed to the clogging of small pores of the support by the grafted or impregnated metal oxide species …”
Section: Resultsmentioning
confidence: 99%